INVENTARISASI EMISI GAS RUMAH KACA SEKTOR LIMBAH DENGAN FIRST ORDER DECAY DI KABUPATEN KARANGASEM - Affan Irfan Fauziawan (Eksergi, 2021)
Waste production increases with the increase in population, urbanization rate and people's income. Garbage is a contributor to greenhouse gas (GHG) emissions which can cause global warming. The Indonesian government is still committed to reducing greenhouse gas emissions and working to reduce / limit the increase in temperature below 1.50C. Karangasem Regency, is on the island of Bali, with a population in 2018 of 414,800 people. The population is spread across 8 sub-districts with the population growth rate in Karangasem averaging 0.88% per year. The distribution of the population will be directly proportional to the distribution of solid waste produced. It is important to do an inventory of GHG emissions to determine the amount of emissions in Karangasem Regency. The method for calculating municipal solid waste will be carried out using the First Order Decay method contained in the IPCC (Intergovernmental Panel on Climate Change) Guidelines. From the calculation results, GHG emissions have been obtained in each sub-district in Karangasem Regency. Total GHG emissions in 2019 amounted to 11,764 tons CO2-e, with the highest GHG emission contributor, namely Karangasem District with 2,302 tons CO2-e and the lowest being Sidemen District with 894 tons CO2-e. With this research, it is hoped that stakeholders will be able to make efforts (mitigation) that can reduce these GHG emissions.